2015
DOI: 10.1101/gad.253534.114
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of pervasive noncoding transcription in embryonic stem cells by esBAF

Abstract: Approximately 75% of the human genome is transcribed, the majority of which does not encode protein.However, many noncoding RNAs (ncRNAs) are rapidly degraded after transcription, and relatively few have established functions, questioning the significance of this observation. Here we show that esBAF, a SWI/SNF family nucleosome remodeling factor, suppresses transcription of ncRNAs from~57,000 nucleosome-depleted regions (NDRs) throughout the genome of mouse embryonic stem cells (ESCs). We show that esBAF funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 67 publications
6
65
1
1
Order By: Relevance
“…A growing body of evidence has indicated that the expression of lncRNAs is tightly regulated through distinct mechanisms, such as chromatin state, transcription factors (TFs), and microRNAs [33]. And majority of lncRNAs are transcribed from antisense regions upstream of promoters, intragenic regions, intergenic regions distal to promoters, or gene bodies of protein-coding genes [7].…”
Section: Characteristics Of Lncrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence has indicated that the expression of lncRNAs is tightly regulated through distinct mechanisms, such as chromatin state, transcription factors (TFs), and microRNAs [33]. And majority of lncRNAs are transcribed from antisense regions upstream of promoters, intragenic regions, intergenic regions distal to promoters, or gene bodies of protein-coding genes [7].…”
Section: Characteristics Of Lncrnasmentioning
confidence: 99%
“…A recent high-throughput transcriptome analysis showed that nearly 75% of the human genome is transcribed into RNAs and only ∼2% of the genome serves as blueprints for proteins with others as non-coding RNAs (ncRNAs) [7]. ncRNAs can be short or small (<200 bp) or long (⩾200 bp) in length.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the lncRNA at PHO84 directly recruits Hda1 is still not clear [14]. It should be noted that, in some cases, the act of lncRNA transcription, rather than the lncRNA products, play regulatory roles [15]. …”
Section: Biological Roles Of Long Noncoding Rnas (Lncrnas)mentioning
confidence: 99%
“…Genome-wide analysis of Isw2 targets revealed that Isw2 functions at NDRs at both the 5′ and 3′ ends of genes [25], and that Isw2 is targeted and represses anti-sense lncRNAs from divergent promoters at the 3′ ends of genes [25,26]. More recently, it was shown that mammalian esBAF, a Swi/Snf family chromatin remodeling factor that is required to maintain embryonic stem cell (ESCs) renewal and pluripotency [27], was found to repress lncRNAs genome-wide [15]. esBAF accomplishes this function by stabilizing nucleosomes at lncRNA initiation sites and maintaining a well-defined NDR [15].…”
Section: Lncrnas Whose Transcription Is Highly Regulatedmentioning
confidence: 99%
See 1 more Smart Citation